Optimization of Au-Free Ohmic Contact Based on the Gate-First Double-Metal AlGaN/GaN MIS-HEMTs and SBDs Process - Hui Sun; Meihua Liu; Liu, Peng; Lin, Xinnan; Jianguo Chen; Wang, Maojun; Dongmin Chen (IEEE TRANSACTIONS ON ELECTRON DEVICES, 2018)
The compatibility of Au-free (Ti/Al/Ti/TiN) ohmic contacts in the gate-first double-metal (GFDM) process for AlGaN/GaN metal-insulator-semiconductor high-electron-mobility transistors (MIS-HEMTs) and Schottky barrier diodes (SBDs) on the same 150-mm wafer was investigated and discussed for the first time, including contact pretreatments, Al diffusion in dielectric layers, and vias (contact windows between two metal layers) etching conditions. All of these steps are crucial to ohmic contacts as well as overall AlGaN/GaN device fabrication process. With the optimized ohmic contacts steps, not only an extremely low ohmic contact resistance (RC) value of 1.07 Omega . mm but also an excellent uniformity on the 150-mm wafer was obtained. The performance and uniformity of the MIS-HEMTs and SBDs based on the optimized GFDM process were also discussed.